Eksistensi Peran Dewan Perwakilan Daerah Republik Indonesia Terhadap Kesejahteraan Dan Pemberdayaan Daerah - Hidayatullah Putra; Desi Hafizah (GLOBAL SCIENTS PUBLISHER, 2025)
The Regional Representative Council of the Republic of Indonesia (DPD RI) plays an important role in realising the welfare and empowerment of regional communities as a representation of regional interests within the state system. Based on the Third Amendment to the 1945 Constitution, the Regional Representative Council of the Republic of Indonesia (DPD RI) is expected to be a link between the central and regional governments to ensure fairness in national development. This research aims to analyse the functions and authorities of the Regional Representative Council (DPD RI) in advocating for regional welfare, as well as the efforts undertaken through legislative, oversight, and policy consideration functions. The method used is normative legal research with a legislative and conceptual approach, utilising primary and secondary legal materials. The research results indicate that the Regional Representative Council (DPD RI) has carried out its functions through the supervision of village funds, the submission of regional island bills, and policy recommendations to the government and the House of Representatives. To increase its effectiveness, it is necessary to strengthen the authority of the DPD RI through a revision of Law MD3.